Symmetric oil price shocks and government expenditure-real exchange rate nexus: ARDL and SVAR models for an oil-based economy, 1970-2018 - Abdulaziz Hamad Algaeed (Cogent Economics & Finance, 2020)
Historically, oil has been the main source of earnings in the Saudi Arabian economy. Different from other symmetric oil price shock studies, the aim of this paper is to test the impacts of symmetric oil price shocks on government expenditure-real exchange rate nexus and ultimately, to check the conformity of symmetric oil price shock findings to those prevailing in literature. To achieve this endeavor, autoregressive distributed lag (ARDL) and structural vector autoregressive (SVAR) have been employed for the period of 1970 to 2018. The goal of carrying out ARDL and SVAR together is to consolidate and strengthen the consistency of the results obtained from both approaches. Our models' findings support the short-run appreciation of the real exchange rate as a reaction to symmetric oil price shocks and to real government expenditure. The latter finding, though is consistent with Dutch disease predictions. However, in the long-run symmetric oil price shocks negate the real exchange rate. The directional map of causality is as follows: symmetric oil price shocks impact the total earnings of the Saudi government and hence, government spending. Thereafter, the composition of expenditure causes an appreciation of the real exchange rate. Policymakers should consider oil price fluctuations as a source of disturbance to government earnings. Solutions could be carried out by benefiting from other countries' experience.
Keywords: C22; C13; E10; G15; F31; 330; Government expenditure; ARDL; oil price; exchange rate; symmetric; SVAR